Diseño del sistema de explotación subterráneo para la extracción de oro del bloque S01 de la sociedad “Las Peñas”, código 591834, sector Chinapintza, cantón Paquisha, Provincia de Zamora Chinchipe - Berru Quizhpe, Bryam Stalin (2024)
The research titled "Design of the Underground Mining System for Gold Extraction from Block S01 of the 'Las Peñas' Company, Code 591834, Chinapintza Sector, Paquisha Canton, Zamora Chinchipe Province" focuses on implementing sequences, cycles, and methods for efficient gold extraction in Block S01. A three-dimensional location was conducted using topography and a geomechanical and geological characterization of the hanging wall and footwall rocks, as well as the mineral body. Parameters such as specific weight and ore grade were analyzed, using 9 samples for index properties and 15 samples for block grade estimation. The pentagonal method by sampling channels was applied to estimate reserves, revealing a total extractable tonnage of 1348 tons, with a thickness of 0.5 m and an average grade of 3.25 gr/Tn. Subsequently, the UBC method was used to determine the most suitable mining system, concluding that the Cut and Fill system is optimal. The design considers minimum dimensions for safe working conditions, drill pattern designs, gallery expansions to accommodate transport equipment, production shafts and personnel passages, and cut galleries necessary for ore extraction. Additionally, the stope design ensures proper ore selection and dilution control, as well as the placement of generated waste to serve as support and ascending advancement, allowing the recovery of 75% of the estimated ore. A cost analysis was conducted to evaluate the project's economic feasibility, covering operating costs such as drilling and blasting, loading, transportation, equipment acquisition, personnel costs, equipment depreciation, and other relevant factors. A sensitivity analysis was also performed to determine the IRR and NPV, assuming an unknown value of 15%, considering various prices and operating costs in $/gr. Keywords: Underground Mining, Sampling Channels, Pentahedral Method, Cut and Fill, IRR, NPV.